Large Cell Neuroendocrine Carcinoma of the Extrahepatic Bile Duct - Ji Young Park; Tae Joo Jeon (The Korean Journal of Gastroenterology, 2018)
Primary neuroendocrine tumors originating from the extrahepatic bile duct are rare. Among these tumors, large cell neuroendocrine carcinomas (NECs) are extremely rare. A 59-year-old man was admitted to Sanggye Paik Hospital with jaundice that started 10 days previously. He had a history of laparoscopic cholecystectomy, which he had undergone 12 years previously due to chronic calculous cholecystitis. Laboratory data showed abnormally elevated levels of total bilirubin 15.3 mg/dL (normal 0.2-1.2 mg/dL), AST 200 IU (normal 0-40 IU), ALT 390 IU (normal 0-40 IU), and gamma-glutamyl transferase 1,288 U/L (normal 0-60 U/L). Serum CEA was normal, but CA 19-9 was elevated 5,863 U/mL (normal 0-37 U/mL). Abdominal CT revealed a 4.5 cm sized mass involving the common bile duct and liver hilum and dilatation of both intrahepatic ducts. Percutaneous transhepatic drainage in the left hepatic duct was performed for preoperative biliary drainage. The patient underwent radical common bile duct and Roux-en-Y hepaticojejunostomy for histopathological diagnosis and surgical excision. On histopathological examination, the tumor exhibited large cell NEC (mitotic index >20/10 high-power field, Ki-67 index >20%, CD56 [+], synaptophysin [+], chromogranin [+]). Adjuvant concurrent chemotherapy and radiotherapy were started because the tumor had invaded the proximal resection margin. No recurrence was detected at 10 months by follow-up CT.